2019
DOI: 10.1148/rg.2019180075
|View full text |Cite
|
Sign up to set email alerts
|

MRI Evaluation of the Response of Rectal Cancer to Neoadjuvant Chemoradiation Therapy

Abstract: MRI plays a critical role in the staging and restaging of rectal cancer. Although newly diagnosed early-stage rectal cancers may immediately be amenable to surgical resection, patients with advanced disease first undergo neoadjuvant therapy that consists of a combination of chemotherapy and radiation therapy. Evaluation of rectal cancer after neoadjuvant therapy is best performed with MRI, given its superior soft-tissue contrast and its ability to allow multiplanar imaging and functional evaluation. In this se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 73 publications
2
39
0
Order By: Relevance
“…CT can be used for imaging of the primary tumor; however, therapy response to RCT can only be visualized indirectly by size measurement as the tumor perfusion and thus its vitality cannot be quantified in single-phase examinations with conventional CT systems (11,12). This drawback of CT could be overcome with dual-energy CT (DE-CT) systems, which have found widespread application in clinical routine in recent years (13).…”
Section: Introductionmentioning
confidence: 99%
“…CT can be used for imaging of the primary tumor; however, therapy response to RCT can only be visualized indirectly by size measurement as the tumor perfusion and thus its vitality cannot be quantified in single-phase examinations with conventional CT systems (11,12). This drawback of CT could be overcome with dual-energy CT (DE-CT) systems, which have found widespread application in clinical routine in recent years (13).…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) of the pelvis is fundamental to the staging and restaging of patients with adenocarcinoma of the rectum [ 1 4 ]. MRI is applied to assess markers, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The article by Kalisz et al (5) in this issue of RadioGraphics provides an excellent, well-written comprehensive review of MRI in the posttherapeutic response assessment of rectal cancer, enriched with several excellent multimodality images. The article begins by providing an over-This copy is for personal use only.…”
mentioning
confidence: 99%
“…As alluded to in the article by Kalisz et al (5), accurate local staging is paramount for allocating patients to the most suitable treatment and cannot be emphasized enough. The results of several studies, including the MERCURY trial, have shown high accuracy of a high-resolution T2-weighted sequence in predicting the risk of circumferential resection margin involvement, which is an independent risk factor for local recurrence (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation